CHALLENGES AND STRATEGIES OF MALAYSIAN AUTOMOTIVE: A LITERATURE REVIEW 2016-2018 - Mohammad Nazir, Norzuliana; Shavarebi, Kamran (Journal of Technology Management and Business, 2019)
Malaysia automotive industry is facing extraordinary challenges from global competition such as foreign brands through trade liberalization and the changes on customer behavior. The National Automotive Policy (NAP) still not fully transformed Malaysian automotive industries into a globally competitive and export-oriented sector. Hence, more research needed to find out more strategies to overcome every single challenge. Hence, this paper aim to study about Malaysia automotive industryâ€™s challenges and strategies comprehensively.Based on findings, there are nine main strategies to overcome various challenges; EEV, ELV, sustainability, performance monitoring, relationship, management, NPD, customer engagement and continuous improvement. Most of the studies related to green such as end-of-life vehicle (ELV), Energy Efficient Vehicles (EEV) and sustainability but still lack of study about new product development (NPD) even though the significance towards industryâ€™s survival. Due to that, further research will investigate on NPD specifically on cross-functional team empirically in the future due to cross-functional team is one of the factors of NPD success.Total 46 the most relevant articles has been chosen from various journals and databases between year 2016 and 2018 with keywords â€œMalaysiaâ€ and â€œAutomotiveâ€ for the most updated review. The challenges and strategies reviewed due to other than as a guidance for further research, it can help companies to improve the strategies suitable with the challenges they are facing. From author knowledge, no studies about comprehensive review on Malaysia automotive industryâ€™s challenges and strategies as most of the study focus on certain topic such as on quality management.